Interval colorectal cancers after negative faecal immunochemical test in a 13-year screening programme. (June 2021) - Zorzi, Manuel; Hassan, Cesare; Senore, Carlo; Capodaglio, Giulia; Turrin, Anna; Narne, Elena; Mussato, Alessio; Rizzato, Silvia; Chinellato, Enrico; Zamberlan, Sara; Repici, Alessandro; Rugge, Massimo
Objective: To assess faecal immunochemical test sensitivity for cancer in a very large population-based cohort followed up for six rounds with biennial faecal immunochemical test repetition. Methods: This study is based on interval colorectal cancers diagnosed in a cohort of subjects aged 50–69 undergoing repeated faecal immunochemical test screening (six rounds) from 2002 to 2015. Test sensitivity was calculated using both the Proportional Interval Cancer Rate and the Interval Cancer Proportion method. Results: Among 441, 647 faecal immunochemical tests (123, 347 individuals), 150 interval colorectal cancers were detected after a negative faecal immunochemical test. Interval colorectal cancer incidence rate was 1.87 per 10, 000 person-years (95%CI: 1.60–2.20), and it was higher during the second interval year (rate ratio: 1.78; 95%CI: 1.28–2.47), for proximal locations (rate ratio: 3.00; 95%CI: 1.92–4.68), and among 60–71 year old subjects (rate ratio: 2.37; 95%CI: 1.61–3.50). The Proportional Interval Cancer Rate was 13.1%, with an overall faecal immunochemical test sensitivity of 86.9% (95%CI: 84.7–89.0). Sensitivity was lowest at the first round (81.5%; 95%CI: 75.6–86.2), and increased to 91.9% (95%CI: 83.9–96.5) for subsequent rounds. Applying the Interval Cancer Proportion method, sensitivity was 83.9% (95%CI: 81.3–86.2), and it was highest at the first round (89.0%; 95%CI: 85.7–91.6), ranging between 73% and 83.1% at subsequent rounds. Conclusions: A faecal immunochemical test sensitivity for cancer higher than 80% resulted in a low incidence of interval colorectal cancers, representing an accurate estimate of one of the major limits of screening programmes. Due to intrinsic biases, the Proportional Interval Cancer Rate and the Interval Cancer Proportion methods generated different trends in faecal immunochemical test sensitivity by screening round.